On a new approach to the study of plane boundary-value problems - Gutlyanskiĭ, V.Ya.; Ryazanov, V.I.; Yefimushkin, A.S. (Reports of the National Academy of Sciences of Ukraine, 2017)
We give a short description of our recent results obtained by a new approach to the boundary-value problems, such as the Dirichlet, Hilbert, Neumann, Poincaré and Riemann problems, for the Beltrami equations and for analogs of the Laplace equation in anisotropic and inhomogeneous media. We show that the approach makes it possible to study many problems of mathematical physics with arbitrary boundary data which are measurable with respect to logarithmic capacity.